PLA Nanofibrous Scaffolds for Full Thickness Wound Healing - Pogorielov, Maksym V.; Deineka, Volodymyr N.; Vasyliev, Roman G.; Zubov, Dmytro A.; Oleshko, Oleksandr N.; Liubchak, Iryna V.; Gubar, Olga S.; Zlatska, Olena V.; Rodnichenko, Anzhela Ye.; Vodsedalkova, Kateryna; Berezkinova, Liliana (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 069–073